Macro Poverty Outlook, Spring Meetings 2022 : Country-by-country Analysis and Projections for the Developing World - World Bank (Washington, DC, 2022)
This edition of the Macro Poverty Outlooks periodical contains 203 country-by-country forecasts and overviews for GDP, fiscal, debt and poverty indicators for developing countries. Macroeconomic indicators such as population, gross domestic product and gross domestic product per capita - and where available – other indicators such as primary school enrollment, life expectancy at birth, total greenhouse gas emissions and inflation, among others, are included for each country. In addition to the World Bank’s most recent forecasts, key conditions and challenges, recent developments and outlook are briefly described for each country.